2018
DOI: 10.15644/asc52/4/6
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of the Students from the School of Dental Medicine in Zagreb towards CAD/CAM

Abstract: AimDue to fast and continuing advances in digital dental technology it is important to provide appropriate CAD/CAM education of preclinical (PS) and clinical (CS) dental students. Therefore, the aim of this study was to determine the knowledge and attitudes on CAD/CAM technology of PS and CS at the School of Dental Medicine, University of Zagreb since the obtained results can show the level of students’ knowledge and possibly a need for additional education.Materials and methodsThis study included 216 undergra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…Few surveys targeted dental students and sought their attitudes towards integration of digital dentistry into dental education and clinical practice, including CAD/CAM technology. The results indicated positive attitudes and a need for greater exposure and integration of CAD/CAM technology into future dental training/education [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few surveys targeted dental students and sought their attitudes towards integration of digital dentistry into dental education and clinical practice, including CAD/CAM technology. The results indicated positive attitudes and a need for greater exposure and integration of CAD/CAM technology into future dental training/education [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published evaluating the incorporation of the CAD/CAM technology into the preclinical and clinical curriculum. 3,[9][10][11][12][13] The studies reported a positive attitude of the students toward the technology but also noted that they felt insufficiently informed and expressed the need for additional education. In a recent 2019 study by Zimmermann et al, fourth-year dental students were introduced to the CAD/CAM technology and their clinical experience was accessed with a questionnaire.…”
Section: Responses From Cad/cam Usersmentioning
confidence: 99%
“…Over the last two decades the demand and application of computer aided design/computer aided manufacturing (CAD/CAM) technology in the field of dentistry has rapidly increased [1] . CAD/CAM technology was launched in 1960's for the purpose of aircraft and automotive industries [2] . In 1971, Dr. Duret was the one who introduced CAD/CAM technology in dentistry and in 1983 first CAD/CAM restoration was made [3] .…”
Section: Introductionmentioning
confidence: 99%